Training and Mentoring Vocational Pharmacy Personnel to Become Responsible for Small Traditional Medicine Businesses - Wibowo, Teguh Setiawan; Rahman, Alief Putriana (Asian Journal of Community Services, 2024)
The aim of training and mentoring activities for vocational pharmaceutical personnel to become people in charge of small traditional medicine businesses are to improve the quality and safety of traditional medicine products as well as improve the technical and managerial skills of vocational pharmaceutical personnel so that they can carry out their role as people in charge effectively. The methods used theoretical presentation sessions, questions/answers and discussions for online training and discussions, FGDs, workshops and case studies for offline mentoring at the Islamic University of Madura which were conducted on 88 students of the diploma three Pharmacy Study Program, Faculty of Health, Islamic University of Madura. The result is community service through training activities and mentoring for pharmaceutical vocational staff to become people in charge of small traditional medicine businesses, receiving an enthusiastic and positive response from the participants present.